Improving physical functional and quality of life in older adults with multiple sclerosis via a DVD-delivered exercise intervention: a study protocol - Wójcicki, Thomas R (BMJ Open, 2014)
INTRODUCTION: There is a need to identify innovative, low-cost and broad-reaching strategies for promoting exercise and improving physical function in older adults with multiple sclerosis (MS). METHODS AND ANALYSIS: This randomised controlled pilot trial will test the efficacy of a 6-month, DVD-delivered exercise intervention to improve functional performance and quality of life in older adults with MS. Participants will be randomised either into a DVD-delivered exercise condition or an attentional control condition. This novel approach to programme delivery provides participants with detailed exercise instructions which are presented in a progressive manner and includes a variety of modifications to better meet varying levels of physical abilities. The targeted exercises focus on three critical elements of functional fitness: flexibility, strength and balance. It is hypothesised that participants who are randomised to the exercise DVD condition will demonstrate improvements in physical function compared with participants assigned to the attentional control condition. Data analysis will include a 2 (condition)×2 (time) mixed factor analysis of variance (ANOVA) that follows intent-to-treat principles, as well as an examination of effect sizes. Participants will take part in qualitative interviews about perspectives on physical activity and programme participation. ETHICS AND DISSEMINATION: The study protocol was approved by a university institutional review board and registered with a federal database. Participants will be asked to read and sign a detailed informed consent document and will be required to provide a physician's approval to participate in the study. The exercise DVDs include an overview of safety-related concerns and recommendations relative to exercise participation, as well as detailed instructions highlighting the proper execution of each exercise presented on screen. Following completion of this trial, data will be immediately analysed and results will be presented at scientific meetings and published in scholarly journals. TRIAL REGISTRATION NUMBER: Clinical Trials NCT01993095.